S129 What proportion of patients with lung cancer would have been eligible for ct screening according to various proposed inclusion criteria?. (15th November 2016) - Gracie, K; Kennedy, M; Ellames, D; Hawramy, B; Al-Ameri, A; Esterbrook, G; Blaxill, P; Smith, G; Smith, P; Naseer, R; Rodger, K; Robson, J; et al.
Abstract : Abstract: The US National Lung Screening Trial (NLST) identified persons for lung cancer screening by age (55–74 yrs) and smoking history, but a subsequent analysis of the US SEER database showed that only 26.7% of lung cancer cases would have been eligible for screening according to these criteria. Strategies to increase the proportion of lung cancer patients who might qualify for screening include increasing the upper age limit to 80 years (endorsed by the US Preventative Services Task Force – USPSTF), and using composite lung cancer risk prediction tools. The UK Lung Screening pilot (UKLS) used the Liverpool Lung Project score (LLP) to identify patients for screening. In a validation cohort from the US Prostate, Lung, Colorectal and Ovarian study, a threshold based on the PLCOM2012 score identified more cancers than the NLST criteria. We prospectively compared these criteria for the first time in patients presenting with lung cancer in Yorkshire. Methods: We audited the proportion of patients presenting with lung cancer through fast-track clinics at 4 Yorkshire centres who would have been eligible for screening according to the following criteria: NLST criteria, UKLS criteria, USPSTF criteria, LLP ≥5% 55–80 yrs, and PLCO ≥1.51% 55–80 yrs. Results: Data was collected for 206 patients presenting between January and July 2016 (Leeds 131, Halifax 26, Bradford 12, Mid-Yorkshire 37). Median age was 72 years and the proportion of cases by age cohort was as follows: <55 yrs 9.2%, 55–60 yrs 9.7%, 61–65 yrs 12.1%, 66–70 yrs 13.6%, 71–75 yrs 18.4%, 76–80 yrs 17.0%, >80 yrs 19.9%. Smoking status was: current smoker 89 (43.2%), ex-smoker 106 (51.5%) and never smoker 11 (5.3%). The number of patients eligible by the various criteria are shown in Table 1 . Conclusion: The proportion of lung cancer patients who would have been eligible for screening differs considerably between the various criteria. Only approximately one third of patients would have been eligible according to the criteria used in NLST and UKLS. Increasing the upper age limit for screening to 80yrs substantially increases the proportion of cases that would be eligible. A threshold of 1.51% by the PLCOM2012 score included the largest number of lung cancer patients of the criteria assessed.